Associations of dietary inflammatory index and composite dietary antioxidant index with erectile dysfunction and the mediating role of metabolic dysregulation: a cross-sectional analysis of NHANES 2001–2004 data - Wang, Lang; Wei, Can; Jing, Junfeng; Ni, Dawei; Shao, Mingmin; Chen, Jingxiong; Wu, Wei; Zhang, Yanbin (Frontiers in Nutrition, 2025)
BackgroundInflammation and oxidative stress are a common and fundamental factor in the pathological process leading to erectile dysfunction (ED) and metabolic dysregulation. We aimed to reveal the relationship between the DII, composite dietary antioxidant index (CDAI), and ED, as well as the mediating role of MS, TyG index, MAP, UA, and TC on this relationship.MethodsThis study included 1,488 participants from the NHANES surveys conducted between 2001 and 2004. The DII was constructed using 27 dietary components related to inflammatory potential, while the CDAI was built using six key minerals and vitamins. In the analysis, Spearman correlation, generalized linear models, and weighted logistic regression models were employed. The mediating roles of metabolic indicators in the relationships were investigated using Causal mediation analysis.ResultsAfter comprehensive adjustment for confounding factors, we found a significant association between DII (OR: 1.07, 95% CI: 1.03–1.11, p < 0.001) and CDAI (OR: 0.97, 95% CI: 0.95–1.00, p < 0.05) and ED. Additionally, all metabolic indicators except for the TyG index (OR: 1.54, 95% CI: 1.20–1.96, p < 0.01), did not show a significant association with the risk of ED. The DIIhigh + CDAIlow group had the highest ED risk. Further mediation analysis indicated that TyG played a mediating role between DII and ED, while MS played a mediating role between CDAI and ED.ConclusionThis study indicates that DII and CDAI were significantly associated with ED.